Lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, preparation method and application
Through the preparation of lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, a porous aromatic framework structure is formed, which solves the problem of insufficient electrochemical performance and stability in lithium-ion batteries, significantly improves the safety and performance of lithium-ion batteries, and realizes the realization of the safety and performance of lithium-ion batteries. Highly efficient lithium ion migration and electrochemical stability.
Patent Information
- Application Number
- CN202310857832.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-07-13
AI Technical Summary
The existing quasi-solid polymer electrolytes have shortcomings in electrochemical performance, thermal stability and flexibility, and there is a serious concentration polarization phenomenon in traditional dual-ion polymer electrolytes, which cannot effectively limit the formation of lithium dendrites, resulting in lithium The safety and performance of ion batteries are difficult to improve at the same time.
The preparation method of lithium-rich PAF composite single-ion quasi-solid polymer electrolyte is adopted. By heating and stirring the combination of lithium-rich PAF material and functional polymer under vacuum conditions, solvents and plasticizers are added to form a porous aromatic framework structure, which is significantly Suppress the polarization phenomenon of concentration difference and improve electrochemical performance.
It achieves high room temperature ion conductivity, low activation energy, good electrochemical stability and high lithium ion migration number, improves the safety and performance of lithium ion batteries, and is simple in preparation and is suitable for industrial production.
Smart Images

Figure CN116706225B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer electrolytes, and in particular relates to a lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, a preparation method and an application thereof. Background Art
[0002] With the rapid development of aerospace, electronic communications, energy industry and other fields, the conversion and storage of renewable energy is an important topic of scientific research today. Due to the characteristics of lithium ions such as high energy density, low self-discharge rate, long cycle life and light weight, they have become the first choice for applications such as portable devices, electric vehicles, and grid energy storage. With the improvement of performance, the safety hazards of lithium-ion batteries have gradually become prominent, such as the flammability and leakage of liquid electrolytes. Therefore, for safety reasons, how to maintain high performance while reducing the proportion of liquid in the electrolyte and ultimately achieve all-solid-state electrolytes is of great significance to the safety and performance improvement of lithium-ion batteries. At the same time, the contradiction between high energy density and high safety needs to be resolved in practical applications. At present, quasi-solid-state polymer electrolytes (QSPE) have advantages in adaptability and safety to current battery technology and are considered to be a promising solution, but they still face many challenges: (1) Li + Low conductivity; (2) Thermal stability, electrochemical stability and flexibility cannot meet the relevant requirements at the same time; (3) Traditional dual-ion polymer electrolytes have serious concentration polarization phenomenon inside, which cannot effectively limit the formation of lithium dendrites. Therefore, how to obtain quasi-solid polymer electrolytes for lithium batteries with excellent electrochemical performance, thermal and electrochemical stability, flexibility and reduced concentration polarization phenomenon is a technical problem that needs to be solved urgently. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, characterized in that its preparation method comprises the following steps:
[0004] Step 1: Under vacuum conditions, the lithium-rich PAF material is heated at 15-40° C. for 20-30 hours, then a solvent is added and stirred for 20-30 hours, and then a functional polymer is added and stirred at 15-40° C. for 40-60 hours, and then vacuum dried at 60-150° C. for 40-60 hours to obtain a polymer electrolyte;
[0005] The solvent is one or any combination of N-pyrrolidone, N,N-dimethylformamide, acetone, and triethylamine; the functional polymer is one or any combination of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and polyvinyl alcohol (PVA), and the mass ratio of the functional polymer to the lithium-rich PAF material is 1 to 25:1;
[0006] Step 2: Under room temperature, the polymer electrolyte obtained in step 1 is immersed in a plasticizer for 10 minutes to 2 hours to obtain a single-ion quasi-solid polymer electrolyte;
[0007] The plasticizer is one or any combination of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DME).
[0008] Furthermore, the preparation method of the lithium-rich PAF material comprises the following steps:
[0009] Step 1:
[0010] Under nitrogen protection, monomer one and monomer two are added to a solvent in a molar ratio of 1:1-3, and then tetrakis(triphenylphosphine)palladium and cuprous iodide are added, and after a cycle of -196°C liquid nitrogen cooling-vacuuming-nitrogen filling-heating and thawing at 40-60°C, and then reacting at 80-120°C for 40-55h, washing, and then vacuum drying at 60-80°C for 12-48h, a PAF material is obtained;
[0011] The monomer 1 is one or any combination of 1,3,5-tri(4-ethynylphenyl)benzene, 1,3,5-triethynylbenzene, and 1,4-diethylbenzene; the monomer 2 is one or any combination of 2,5-dibromo-p-phenylenediamine, 2,5-dibromoaniline, and 3,6-dibromo-1,2-phenylenediamine; the solvent is one or any combination of methanol, N,N-dimethylformamide, acetonitrile, acetone, triethylamine, and N-pyrrolidone; according to the mass ratio, the monomer 1: monomer 2: tetrakis(triphenylphosphine)palladium: cuprous iodide is 1-5: 1.5-5: 0.1-1: 0.1-1.5;
[0012] Step 2:
[0013] Under nitrogen protection, the PAF material obtained in step 1 is mixed with lithium hydride in a solvent, reacted at 60-80° C. for 2-5 hours, and then 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium (LiCPSI) is added, reacted at 80-100° C. for 36-48 hours, washed, and vacuum dried at 60-80° C. for 12-48 hours to obtain a lithium-rich PAF material;
[0014] The solvent is one or any combination of N,N-dimethylformamide, acetonitrile, acetone or N-pyrrolidone;
[0015] The mass ratio of the PAF material to lithium hydride is 1:3-10;
[0016] The mass ratio of the PAF material to LiCPSI is 1:1.5-10;
[0017] The lithium-rich PAF material structure is a porous aromatic skeleton.
[0018] The present invention also provides an application of a lithium-rich PAF composite single-ion quasi-solid polymer electrolyte in a lithium-ion battery.
[0019] Beneficial effects of the present invention:
[0020] Compared with the prior art, the present invention, through the synergistic effect of raw materials, reaction ratio and process, makes the lithium-rich PAF composite single-ion quasi-solid polymer electrolyte have the following advantages:
[0021] The present invention obtains a series of PAFs materials with different amino content, the amino content is 2.92-9.8mmolg -1 . After lithiation, a single-ion porous aromatic skeleton material PAF-Li is obtained, which is then compounded with PVDF-HFP to obtain a quasi-solid polymer electrolyte PAF-QSPE. Since PAFs have different numbers of functional groups and specific surface areas, they can achieve precise control of the lithium content while being lithium-rich and enhance the electrochemical properties of the polymer electrolyte. PAF-Li fixes anions on the skeleton to form a single-ion system through post-modification, significantly suppressing concentration polarization and improving the stability of the polymer electrolyte. It has been found through testing that the single-ion quasi-solid polymer electrolytes obtained by the present invention have good electrochemical properties, and the room temperature ionic conductivity is 8.48×10 -5 —1.17×10- 4 S cm -1 , which is much higher than the room temperature ionic conductivity of conventional polymer solid electrolytes (SPE) (~10 -6 ), fitting the Arrhenius equation to obtain an activation energy of 0.078-0.093 eV, which has a lower activation energy than the prior art and is beneficial to Li + Dissociation and movement, the lithium ion migration number is 0.82-0.92, which is much higher than the lithium ion migration number of the traditional dual-ion polymer electrolyte system (~0.3), and the initial discharge specific capacity at 0.2C is ~162mAh g -1 After 350 cycles, the capacity retention rate is ~98%, and the Coulomb efficiency is stably maintained at 100%.
[0022] 2. The quasi-solid polymer electrolyte preparation method of the present invention is simple, has high yield, and has a wide source of raw materials. It can accurately control the lithium content in the PAFs material as required. It has good application prospects in the field of lithium-ion batteries and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a comparison diagram of infrared spectra of PAF-221, PAF-221-Li, acetylene monomer and amino monomer obtained in Example 1 of the present invention;
[0024] Figure 2 This is a cycle performance curve of the single-ion quasi-solid polymer electrolyte PAF-221-QSPE obtained in Example 1 of the present invention after being assembled into a battery;
[0025] Figure 3 This is a rate performance curve diagram of the single-ion quasi-solid polymer electrolyte PAF-221-QSPE obtained in Example 1 of the present invention after being assembled into a battery;
[0026] Figure 4 The Arrhenius equation diagram of the AC impedance spectrum of the single-ion quasi-solid polymer electrolyte PAF-221-QSPE obtained in Example 1 of the present invention after being assembled into a battery;
[0027] Figure 5 This is an electrochemical window test curve diagram of the single-ion quasi-solid polymer electrolyte PAF-221-QSPE obtained in Example 1 of the present invention after being assembled into a battery. DETAILED DESCRIPTION
[0028] Example
[0029] The present invention is further described below by means of specific examples. These examples are only intended to illustrate the present invention but are not intended to limit the scope of the present invention.
[0030] Example 1
[0031] (1) Under nitrogen purge, 1,3,5-tri(4-ethynylphenyl)benzene (378 mg) and 2,5-dibromo-p-phenylenediamine (399 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (the volume ratio of DMF to triethylamine was 1:1), and tetrakis(triphenylphosphine)palladium (75 mg) and cuprous iodide (25 mg) were added; after a cycle of -196°C liquid nitrogen cooling-vacuuming-nitrogen filling-50°C heating and thawing, the mixture was reacted at 100°C for 48 hours, washed with a DMF / acetonitrile mixed solution and methanol with a volume ratio of 1:1, and then vacuum dried at 60°C for 12 hours to obtain PAF-221;
[0032] (2) Under nitrogen protection, 100 mg of the PAF-221 material obtained in step (1) was mixed with 500 mg of lithium hydride in 20 mL of DMF, reacted at 60° C. for 3 h, and then 315 mg of LiCPSI was added. The mixture was reacted at 90° C. for 48 h. After washing with ethanol and water, the mixture was vacuum dried at 60° C. for 12 h to obtain a PAF-221-Li material having the following structure:
[0033]
[0034] (3) Under vacuum conditions, 26.6 mg of PAF-221-Li material obtained in step (2) was stirred at room temperature for 24 h, then 2.25 mL of N-pyrrolidone (NMP) was added and stirred for 24 h, then 106.4 mg of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) was added and stirred at room temperature for 48 h, and then vacuum dried at 100 ° C for 48 h to obtain a polymer electrolyte PAF-221-SPE;
[0035] (4) At room temperature, PAF-221-SPE was immersed in plasticizer (ethylene carbonate / propylene carbonate) EC / PC, volume ratio of 1:1) for 1 h to obtain the quasi-solid polymer electrolyte PAF-221-QSPE. Its ionic conductivity at room temperature is 1.17×10 -4 S cm -1 , the activation energy is 0.078eV, and the initial discharge capacity at 0.2C is 162mAh g -1 After 350 cycles, the capacity is 160 mAh g -1 , the retention rate is 98%, the lithium ion migration number is 0.92, and the electrochemical window is 4.55V.
[0036] Example 2
[0037] (1) Under nitrogen purge, 1,3,5-triethynylbenzene (150 mg) and 2,5-dibromo-p-phenylenediamine (399 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (the volume ratio of DMF to triethylamine was 1:1.2), and tetrakis(triphenylphosphine)palladium (80 mg) and cuprous iodide (30 mg) were added; after a cycle of -196°C liquid nitrogen cooling-vacuuming-nitrogen filling-45°C heating and thawing, the mixture was reacted at 90°C for 40 hours, washed with DMF, acetonitrile and methanol, and vacuum dried at 70°C for 24 hours to obtain PAF-222;
[0038] Under nitrogen protection, 100 mg of the PAF-222 material obtained in step (1) was mixed with 600 mg of lithium hydride in 20 mL of DMF, reacted at 65° C. for 2 h, and then 553 mg of LiCPSI was added. The mixture was reacted at 95° C. for 36 h. After washing with ethanol and water, the mixture was vacuum dried at 70° C. for 24 h to obtain a PAF-222-Li material having the following structure:
[0039]
[0040] (2) Under vacuum conditions, 19.95 mg of PAF-222-Li material obtained in step (2) was stirred at room temperature for 36 h, then 2.25 mL of N-pyrrolidone (NMP) was added and stirred for 36 h, then 113.05 mg of PVDF-HFP was added and stirred at room temperature for 36 h, and then vacuum dried at 120 ° C for 48 h to obtain a polymer electrolyte PAF-222-SPE;
[0041] (3) At room temperature, PAF-222-SPE was immersed in plasticizer (EC / PC, volume ratio of 1:1.2) for 2 h to obtain quasi-solid polymer electrolyte PAF-222-QSPE. Its ionic conductivity at room temperature is 8.77×10 -5 S cm -1 , the activation energy is 0.086eV, and the initial discharge capacity at 0.2C is 152mAh g -1 After 350 cycles, the capacity is 143 mAh g -1 , the retention rate is 94%, the lithium ion migration number is 0.82, and the electrochemical window is 4.5V.
[0042] Example 3
[0043] (1) Under nitrogen purge, 1,3,5-tri(4-ethynylphenyl)benzene (378 mg) and 2,5-dibromoaniline (376 mg) were added to a mixed solution of N,N-dimethylformamide (DMF) and triethylamine (the volume ratio of DMF to triethylamine was 1.2:1), and tetrakis(triphenylphosphine)palladium (85 mg) and cuprous iodide (35 mg) were added; after a cycle of -196°C liquid nitrogen cooling-vacuuming-nitrogen filling-60°C heating and thawing, the product was reacted at 95°C for 48 hours, and the product was repeatedly washed with a DMF / acetonitrile mixed solution and methanol with a volume ratio of 2:1, and vacuum dried at 65°C for 20 hours to obtain PAF-223;
[0044] (2) Under nitrogen protection, 100 mg of the PAF-223 material obtained in step (1) was mixed with 400 mg of lithium hydride in 20 mL of DMF, reacted at 70° C. for 4 h, and then 165 mg of LiCPSI was added. The mixture was reacted at 100° C. for 36 h. After washing with ethanol and water, the mixture was vacuum dried at 70° C. for 36 h to obtain a PAF-223-Li material having the following structure:
[0045]
[0046] (3) Under vacuum conditions, 13.3 mg of PAF-223-Li material obtained in step (2) was heated at 40°C for 36 h, and then 2.25 mL of N-pyrrolidone (NMP) was added and stirred for 36 h, and then 119.7 mg of PVDF-HFP was added and stirred at 25°C for 48 h, and then vacuum dried at 110°C for 60 h to obtain a polymer electrolyte PAF-223-SPE;
[0047] (4) At room temperature, PAF-223-SPE was immersed in plasticizer (EC / PC, volume ratio of 1.2:1) for 30 min to obtain quasi-solid polymer electrolyte PAF-223-QSPE. Its ionic conductivity at room temperature is 8.48×10 -5 S cm -1 , the activation energy is 0.093eV, and the initial discharge capacity at 0.2C is 144mAh g -1 After 350 cycles, the capacity is 132 mAh g -1 , the retention rate is 92%, the lithium ion migration number is 0.86, and the electrochemical window is 4.4V.
[0048] Comparative Example 1 (Single-ion quasi-solid polymer electrolyte)
[0049] Article title: Li2Sn2(bdc)3(H2O) x Quasi-solid-state electrolytes of metal organic frameworks for lithium metal batteries x Metalorganic Frameworks for Lithium Metal Battery
[0050] Journal: Electroanalysis 2022, 34, 1667-1672
[0051] Author: Ziwei Guo, Yuanqin He, Daxu Zhang, et al.
[0052] Methods: An aqueous solution of MOF (Li2Sn2(bdc)3(H2O)xa (LS-a) and polytetrafluoroethylene (PTFE) was uniformly dispersed in an excess ethanol solution with a LS-a / PTFE mass ratio of 4:1. The solution was left in the air to evaporate the excess ethanol, thereby turning the solution into a slurry. The slurry was then rolled into a 0.1-0.12 mm thick LSa / PTFE membrane. The membrane was then cut into 16 mm pellets and vacuum dried at 60°C overnight to remove the ethanol. Subsequently, the LS-a / PTFE pellets were treated with an excess of liquid electrolyte (LiPF6 dissolved in a mixed solvent of EC, DMC, and EMC, in a volume ratio of V / cm2). EC :V DMC :V EMC =1:1:1, LiPF6 concentration is 1 mol L -1 ) for 12 hours to obtain a liquid electrolyte film (denoted as LPF@LS-a). The ionic conductivity of the LPF@LS-a film assembled button cell is 4.8×10 -5 S cm -1 , the lithium ion migration number is 0.61, and it has excellent electrochemical stability at room temperature.
[0053] Compared with the ionic conductivity and lithium ion transference number of the quasi-solid polymer electrolyte in Comparative Example 1, the minimum ionic conductivity of the quasi-solid polymer electrolyte obtained in the embodiment of the present invention is 8.48×10 -5 S cm -1 , Li + The lowest migration number is 0.82, which is higher than the electrolyte ion conductivity (4.8×10 -5 S cm -1 ) and Li + Migration number (t Li + =0.61), indicating that the single-ion quasi-solid polymer electrolyte prepared in the present invention has excellent electrochemical stability.
[0054] Comparative Example 2
[0055] Article title: Semi-IPN structured single-ion conductive polymer electrolyte for lithium ion batteries.
[0056] Journal: ChemElectroChem
[0057] Author: Xiu Shen, Longqing Peng, Ruiyang Li, et al.
[0058] Methods: Gradient ratio PEO (Mn = 600,000, EKEAR, Shanghai, China) and cross-linked PAMPS-Li powder were dispersed in ethanol, and then water was slowly added to form a 3D semi-IPN structure mixture. The mixture was magnetically stirred for 4 h to obtain a uniform and viscous hydrogel. The gel was then scraped on a glass plate. Since the water in PEO is not easy to remove, it was air-dried and the ion conductor membrane was peeled off. It was stored in a vacuum oven at 60°C for 3 days to ensure sufficient drying, and then the (SI)2PE film was obtained. The dried (SI)2PE film was sandwiched between the cathode and the anode. In order to enable lithium ions to transport in the positive electrode and improve the interfacial compatibility, a plasticizer was added between the (SI)2PE and the positive electrode interface to assemble a quasi-solid battery. The plasticizer was composed of ethyl carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1. The ionic conductivity of the button cell assembled with the (SI)2PE film was 1.34×10 at 60°C. -5 S cm -1 The lithium ion conductive membrane has lithium ion dominant conductivity, and the lithium ion migration number is 0.77. In addition, the cycling results of the LiFePO4 / Li battery show that the discharge capacity after 100 cycles at a rate of 0.2C is as high as 140.0mAh g -1 , with a retention rate of 90.4%.
[0059] According to prior art reports, the higher the temperature, the higher the electrolyte ion conductivity. Compared with the ion conductivity of the single ion polymer electrolyte in Comparative Example 2, which is 1.34×10 -5 S cm -1 The minimum ionic conductivity of the quasi-solid polymer electrolyte prepared in the embodiment of the present invention at room temperature is 8.48×10 -5 S cm -1 , Li + The lowest migration number is 0.82, which is much higher than the ionic conductivity and Li + Migration number (t Li + =0.77), indicating that the single-ion quasi-solid polymer electrolyte prepared in the present invention has excellent electrochemical stability.
[0060] manual Figure 1 Infrared test
[0061] like Figure 1 As shown, it can be observed that the acetylene monomer is located at 2100 cm -1 The stretching vibration absorption peak of the C≡C bond of the monosubstituted alkyne at 3260 cm -1The ≡CH stretching vibration absorption peak is located at 3300-3500cm in the amino monomer. -1 The characteristic double peaks of -NH2 can be attributed to the range of 2100cm -1 and 3260cm -1 The stretching vibration absorption peak at 2200cm -1 The C≡C stretching vibration absorption peak of disubstituted alkynes appears at 3300 to 3500 cm -1 The amino doublet peak at 1100 to 1150 cm-1 indicates the successful synthesis of PAF-221. After grafting lithium salt to obtain PAF-221-Li, the amino doublet peak becomes a singlet peak at 1100 to 1150 cm-1. -1 The symmetric stretching vibration absorption peak at 1500 cm-1 is attributed to SNS. -1 The characteristic peak near is attributed to the S=O double bond, indicating that the lithium salt is successfully grafted into the PAFs material.
[0062] manual Figure 2 Cyclic performance test
[0063] LiFePO4 was used as the positive electrode and lithium foil as the negative electrode to assemble Li / PAF-221-QSPE / LFP CR2025 button cell, and its cycle performance was tested. Figure 2 As shown, at 0.2C (1C = 175 mAh g -1 ), Example 1 PAF-221-QSPE initial specific capacity is 162 mAh g -1 After 350 cycles, it remained basically stable, with a capacity retention rate of 98% and a Coulombic efficiency of 100%, indicating that PAF-221-QSPE has good electrochemical stability.
[0064] manual Figure 3 Rate performance test
[0065] Figure 3 The rate performance of PAF-221-QSPE at different current densities of Example 1. At different rates, this polymer electrolyte has good performance. At current densities of 0.2, 0.5, 0.8, 1, 2, and 3C, the reversible specific capacities of PAF-221-QSPE are 161, 154, 146, 132, 111, and 92 mAh g, respectively. -1 When the current density returned to 0.2C, the discharge capacity returned to 154 mAh g -1 , the capacity recovery rate reaches 95%.
[0066] manual Figure 4 Arrhenius equation diagram;
[0067] In order to further study the movement mode inside the QSPE, the logarithm of the ionic conductivity σ is fitted with 1000 / T, as shown in Figure 4 As shown, it can be observed that the fitting curve conforms to the Arrhenius equation, indicating that Li + The transmission inside the PAF-221-QSPE obtained in Example 1 follows a hopping mechanism. The activation energy E of the PAF-221-QSPE obtained in Example 1 is calculated to be 0.078 eV. The lower activation energy is beneficial to Li + Dissociation and transfer.
[0068] manual Figure 5 Electrochemical window test curve.
[0069] Linear sweep voltammetry (LSV) was used to measure the electrochemical stability window of the single-ion quasi-solid polymer electrolytes prepared in Examples 1 to 3. Linear sweep voltammetry was used to detect the redox reaction inside the battery. Figure 5 As shown, the electrochemical window of PAF-221-QSPE obtained in Example 1 is stabilized at 4.55V, and there is no oxidation leakage current, indicating that it has good electrochemical stability. At the same time, there is no oxidation leakage current, indicating that the single-ion quasi-solid polymer electrolyte prepared in the present invention has excellent electrochemical stability.
[0070] In summary: compared with the prior art, the electrochemical properties of the materials obtained in the embodiments of the present invention are better than those of the materials obtained in the comparative examples; in addition, the raw material reaction ratios, process conditions and parameters used in Examples 1-3 of the present invention are different, among which the electrochemical stability of the single-ion quasi-solid-state polymer electrolyte obtained in Example 1 is the best among all the embodiments. It can be concluded that the performance of the single-ion quasi-solid-state polymer electrolyte obtained in the present invention is determined by the synergistic effect of the raw materials, reaction ratios, process conditions and parameters.
Claims
1. A lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, characterized in that: Its preparation method comprises the following steps: Step 1: Under vacuum conditions, the lithium-rich PAF material is heated at 15-40° C. for 20-30 hours, then a solvent is added and stirred for 20-30 hours, and then a functional polymer is added and stirred at 15-40° C. for 40-60 hours, and then vacuum dried at 60-150° C. for 40-60 hours to obtain a polymer electrolyte; The solvent is one or any combination of N-pyrrolidone, N,N-dimethylformamide, acetone, and triethylamine; the functional polymer is one or any combination of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), and polyvinyl alcohol (PVA), and the mass ratio of the functional polymer to the lithium-rich PAF material is 1 to 25:1; Step 2: Under room temperature, the polymer electrolyte obtained in step 1 is immersed in a plasticizer for 10 minutes to 2 hours to obtain a single-ion quasi-solid polymer electrolyte; The plasticizer is one or any combination of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene glycol dimethyl ether (DME); The preparation method of the lithium-rich PAF material described in step 1 comprises the following steps: (1) Under nitrogen protection, monomer 1 and monomer 2 are added to a solvent in a molar ratio of 1:1 to 3, and then tetrakis(triphenylphosphine)palladium and cuprous iodide are added, and after a cycle of -196°C liquid nitrogen cooling - vacuuming - nitrogen filling - heating and thawing at 40 to 60°C, the reaction is continued at 80 to 120°C for 40 to 55 hours, and then washed and vacuum dried at 60 to 80°C for 12 to 48 hours to obtain a PAF material; The monomer 1 is one or any combination of 1,3,5-tri(4-ethynylphenyl)benzene, 1,3,5-triethynylbenzene, and 1,4-diethylbenzene; the monomer 2 is one or any combination of 2,5-dibromo-p-phenylenediamine, 2,5-dibromoaniline, and 3,6-dibromo-1,2-phenylenediamine; the solvent is one or any combination of methanol, N,N-dimethylformamide, acetonitrile, acetone, triethylamine, and N-pyrrolidone; according to the mass ratio, the monomer 1: monomer 2: tetrakis(triphenylphosphine)palladium: cuprous iodide is 1-5: 1.5-5: 0.1-1: 0.1-1.5; (2) Under nitrogen protection, the PAF material obtained in step (1) is mixed with lithium hydride in a solvent, reacted at 60-80° C. for 2-5 h, and then 3-chloropropanesulfonyl (trifluoromethanesulfonyl) imide lithium (LiCPSI) is added, reacted at 80-100° C. for 36-48 h, washed, and vacuum dried at 60-80° C. for 12-48 h to obtain a lithium-rich PAF material; The solvent is one or any combination of N,N-dimethylformamide, acetonitrile, acetone or N-pyrrolidone; The mass ratio of the PAF material to lithium hydride is 1:3-10; The mass ratio of the PAF material to LiCPSI is 1:1.5-10; The lithium-rich PAF material structure is a porous aromatic skeleton.
2. Application of the lithium-rich PAF composite single-ion quasi-solid polymer electrolyte described in claim 1 in lithium-ion batteries.
Citation Information
Patent Citations
Single-ion quasi-solid polymer electrolyte, preparation method and application thereof
CN116014237A